KONSEP MANUSIA MENURUT PANDANGAN PSIKOANALISIS DAN BEHAVIORISME - Nurma Nawariah (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
This study aims to determine the human concept according to Psychoanalytic Theory and Behaviorism.This study aims to determine the meaning of Psychoanalysis and the notion of Behaviorism. This research is a library research (library research). The results showed that: Psychoanalytic theory has several main concepts that are unique and different from other personality theories. According to Freud, these concepts are divided into 3 levels; First, awareness (conscious), which is everything that is realized related to meaning in everyday life; Second, namely Pre-conscious which is a layer of the soul below consciousness, and is in the middle between conscious and unconscious; and third, namely the unconscious which is the largest layer of mental life and is below the surface of the water. In addition, the unconscious is also a major part of psychoanalytic theory, which contains instincts or experiences. With words, memories are very difficult to appear in consciousness.